Fentanyl transdermal patches: Extraction and evaluation of a novel disposal method using NarcX®. Issue 1 (26th October 2021) - Palmer, Corianna M.; Canfield, Jeremy R.; Sprague, Jon E.; Oechsle, Crystal M.; Worst, Travis J.
Abstract: Currently, there is no known commercially available product for disposing of used fentanyl transdermal patches. To eliminate the potential for harm and abuse, a proper disposal method is needed–one that neutralizes the dangerous amount of residual fentanyl that remains after therapeutic use of the fentanyl patch. The patent‐pending liquid solution of activated carbon, known as NarcX ®, was investigated as a potential fentanyl adsorbing agent. In order to determine the amount of fentanyl remaining after a patch is treated with NarcX ®, here, we utilized hexanes to first dissolve the patch adhesive and then followed with liquid‐liquid extraction with methanol to recover the fentanyl. Using liquid chromatography coupled to tandem mass spectrometry (LC/MS‐MS), the extracts obtained with this method yielded between 85% and 117% recovery of fentanyl from new and unused patches. Further optimization of this method allowed for a quantitative evaluation of NarcX ® ‐treated fentanyl patches. 100 µg/h Apotex brand fentanyl patches were exposed to NarcX ® for 1, 24, 48, and 72 h. NarcX ® was shown to adsorb fentanyl from the patches with varying degrees of success, demonstrating an average of 66.98 ± 0.75% fentanyl adsorption after 72 h. These findings suggest that more work is needed to successfully neutralize the fentanyl patches in their entirety using NarcX ® ; however, this work does demonstrate proof of concept.